Exploring the elusive composition of corpora amylacea of human brain - Augé, Elisabet (Sci Rep, 2018)
Corpora amylacea (CA) are polyglucosan bodies that accumulate in the human brain during ageing and are also present in large numbers in neurodegenerative conditions. Theories regarding the function of CA are regularly updated as new components are described. In previous work, we revealed the presence of some neo-epitopes in CA and the existence of some natural IgM antibodies directed against these neo-epitopes. We also noted that these neo-epitopes and IgMs were the cause of false staining in CA immunohistochemical studies, and disproved the proposed presence of β-amyloid peptides and tau protein in them. Here we extend the list of components erroneously attributed to CA. We show that, contrary to previous descriptions, CA do not contain GFAP, S100, AQP4, NeuN or class III β-tubulin, and we question the presence of other components. Nonetheless, we observe that CA contains ubiquitin and p62, both of them associated with processes of elimination of waste substances, and also glycogen synthase, an indispensable enzyme for polyglucosan formation. In summary, this study shows that it is imperative to continue reviewing previous studies about CA but, more importantly, it shows that the vision of CA as structures involved in protective or cleaning mechanisms remains the most consistent theory.